Source-specific nitrate and nitrite intakes and associations with sociodemographic factors in the Danish Diet Cancer and Health cohort - Erichsen, Dorit W.; Pokharel, Pratik; Kyrø, Cecilie; Schullehner, Jörg; Zhong, Liezhou; Bondonno, Catherine P.; Dalgaard, Frederik; Fjeldstad Hendriksen, Peter; Sigsgaard, Torben; Hodgson, Jonathan M.; Olsen, Anja; Tjønneland, Anne; et al. (Frontiers in Nutrition, 2024)
The dietary source and intake levels of nitrate and nitrite may govern its deleterious versus beneficial effects on human health. Existing evidence on detailed source-specific intake is limited. The objectives of this study were to assess nitrate and nitrite intakes from different dietary sources (plant-based foods, animal-based foods, and water), characterise the background diets of participants with low and high intakes, and investigate how sociodemographic and lifestyle factors associate with intake levels.In the Danish Diet, Cancer and Health Cohort, sociodemographic and lifestyle information was obtained from participants at enrolment (1993 -1997). Source-dependent nitrate and nitrite intakes were calculated using comprehensive food composition databases, with tap water nitrate intakes estimated via the national drinking water quality monitoring database linked with participants' residential addresses from 1978 -2016. Underlying dietary patterns were examined using radar plots comparing high to low consumers while sociodemographic predictors of source-dependent nitrate intakes were investigated using linear regression models.In a Danish cohort of 55,754 participants aged 50-65 at enrolment, the median [IQR] intakes of dietary nitrate and nitrite were 58. 13 [44.27 -74.90] mg/d and 1. 79 [1.43 -2.21] mg/d, respectively. Plant-based foods accounted for ~76% of nitrate intake, animal-based foods ~10%, and water ~5%. Nitrite intake was sourced roughly equally from plants and animals. Higher plant-sourced nitrate intake was associated with healthier lifestyles, better dietary patterns, more physical activity, higher education, lower age and lower BMI. Females and participants who had never smoked also had significantly higher plant-sourced nitrate intakes. Higher water-sourced nitrate intake was linked to sociodemographic risk factors (smoking, obesity, lower education). Patterns for animal-sourced nitrate were less clear.Conclusions: Participants with higher plant-sourced nitrate intakes tend to be healthier while participants with higher water-sourced nitrate intakes tended to be unhealthier than their low consuming counterparts. Future research in this cohort should account for the sociodemographic and dietary predictors of source-specific nitrate intake we have identified.